1976
DOI: 10.1037/0022-3514.34.3.317
|View full text |Cite
|
Sign up to set email alerts
|

Sex and social class as determinants of future orientation (time perspective) in adolescents.

Abstract: Hypotheses concerning the effects of sex and class On future orientation were tested on 100 boys and girls between the ages of 14 and 16. Future orientation was measured in various domains of life, constituting either private or public areas of concern (e.g., family, environment), on the dimensions of density (number oi hopes and fears voiced by the subject), extension, and optimismpessimism. As predicted, middle-class adolescents, as compared with lowerclass adolescents, voiced more hopes and fears relating t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
1
5

Year Published

1984
1984
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(64 citation statements)
references
References 16 publications
(18 reference statements)
4
54
1
5
Order By: Relevance
“…The Pacific sociocultural context, in particular, serves as a critical point in which FTP may apply and assist individuals in their academic learning and professional development. There is evidence to indicate that FTP originates in a sociocultural context (Lamm, Schmidt, & Trommsdorff, 1976;Seijts, 1998;Vázquez & Rapetti, 2006). Accordingly, as an outcome of socialisation, individuals who are more 'socialised' will have learned that their social and cultural class as well as society, in general, expect certain goals and events, some of which are more time specific than others.…”
Section: The Pacific Context: Ftp and Its Relevancementioning
confidence: 99%
“…The Pacific sociocultural context, in particular, serves as a critical point in which FTP may apply and assist individuals in their academic learning and professional development. There is evidence to indicate that FTP originates in a sociocultural context (Lamm, Schmidt, & Trommsdorff, 1976;Seijts, 1998;Vázquez & Rapetti, 2006). Accordingly, as an outcome of socialisation, individuals who are more 'socialised' will have learned that their social and cultural class as well as society, in general, expect certain goals and events, some of which are more time specific than others.…”
Section: The Pacific Context: Ftp and Its Relevancementioning
confidence: 99%
“…Lower class young women were more optimistic about the future than their middle class same-sex peers. Lamm et al (1976) suggested that the optimism of the lower class young women indicated that these young women had less knowledge of the struggles ahead of them than did the middle class young women. They wrote that concerns about balancing career and family might be more salient for the middle class women than the lower class women because the former are likely striving for more challenging careers.…”
Section: Fto Research That Examines Adolescents' Future Plans Hopesmentioning
confidence: 99%
“…This work, which examines sociocultural phenomena in addition to gender, is reviewed next. Lamm et al (1976) studied the FTO of lower and middle class West German male and female students who were 14 and 16 years old. The adolescents were asked about their future orientation in regard to the private (e.g., family), career, and public service domains.…”
Section: Fto Research That Examines Adolescents' Future Plans Hopesmentioning
confidence: 99%
“…The criticism on this approach-that the LSS technique assumes that an individual has only one time horizon that functions for every area in his life (Kasakos 1971)-can be avoided by focusing only on one of the six areas where a certain time perspective may be maintained, namely family, personal development, work Weld, economics, environment, and politics (Lamm et al 1976). In the context of this research, this means focusing on the work Weld of forest managers.…”
Section: Theoretical Backgroundmentioning
confidence: 99%